Academic performance on physics subject of high school students - Monier, Yoan Pablo Rodriguez (International Journal of Psychosocial Rehabilitation, 2020)
An investigation was conducted to assess how academic performance behaved in the subject of physics in students of high school. The bibliographic review was used to know how the levels of performance in the 2016-2017, 2017-2018, 2018-2019 periods; In addition, the qualitative and quantitative method was applied to compare the results obtained in the students of I, II and III level, of the Captain Giovanny Calles Educational Unit, noting that there are no significant differences in the I and II levels, in the III level There is a slight improvement that may be associated with the students have made an effort to achieve qualifications that allow them to graduate, the preparation of preparatory courses for the Be Bachelor test and guarantee their entrance to the university.